The Learning Curve of Total Laparoscopic Hysterectomy in a Rural Hospital - İsmail Biyik; Mustafa Albayrak; Fatih Keskin; Ayse Nur Usturali Mut (Medical Network, 2020)
OBJECTIVES: Online education and certification programs which help most gynecologic surgeons to advance, improve and prove their skills. However, the benefits of such distant programs in terms of complication rate and operation time has not been evaluated so far. The aim of this study was to report the improvement of a single surgeon's learning curve in total laparoscopic hysterectomy who had no previous mentorship/fellowship education, working in a rural district hospital before and after the completion of a distant on-line education and certification program - Gynaecological Endoscopic Surgical Education and Assessment. STUDY DESIGN: Medical records of patients who underwent total laparoscopic hysterectomy between May 2015 and December 2018 were retrospectively reviewed and grouped based on the certification date of the surgeon, Group 1 before and Group 2 after certification. Groups were compared for variables that impact the learning curve (operation time, complications and conversion to laparotomy) RESULTS: Of the 57 women eligible for evaluation 30 had total laparoscopic hysterectomy in Group 1 and 27 had total laparoscopic hysterectomy in Group 2. BMI, number of vaginal/cesarean births, previous abdominal/pelvic surgeries, operation indications, uterine weight, adnexectomy, and adhesiolysis rates, transfusion requirements, and the decrease in hemoglobin before and after operation were similar between the groups (p>0.05). Operation time was significantly shorter in Group 2 (83 min vs.116 min, p<0.0001). CONCLUSION: Thirty total laparoscopic hysterectomy operations seem enough to reach a plateau in the learning curve for gynecologists working in rural areas with limited facilities who cannot afford lengthily and expensive fellowship/mentorship programs, after completing distant online certification programs.